Identification and Validation of Requirements for a Registry System of Children's Developmental Motor Disorders in Iran - Gozali, Elahe; Safdari, Reza; Ghazisaeedi, Marjan; Rahimi, Bahlol; Eslamlou, Hamidreza Farrokh; Mehraeen, Esmaeil (Methods of Information in Medicine, 2019)
Background Despite recent advances in the field of medical sciences, children's developmental motor disorders (DMDs) are considered as one of the challenges in this area. Establishment of electronic systems for recording and monitoring children's DMDs can play an effective role in identifying patients and reducing the costs and consequences of the disease management. The aim of this study was to identify and validate the requirements for a registry system of children's DMDs in Iran.Methods The present descriptive–analytical study was performed in three main stages. In the first step, the literature was reviewed to identify the requirements. In the second stage, the information obtained from the literature review was used to develop a questionnaire for validating and selecting the requirements for an electronic system of recording DMDs in infants. In the final stage, the requirements were validated by selected experts (22 specialists). Data were analyzed using SPSS 20 software (IBM Corporation, New York, United States).Results According to findings, the requirements of a registry system for children's DMDs were identified in three areas of demographic (24 data elements), clinical data (87 data elements), and technical (28 capabilities). In the demographic section, data elements of “family history of motor disorders” (mean = 1.18) and “drug allergy” (mean = 2.9) gained an average score of < 2.5 and therefore were not selected as data elements necessary for the registry system of data recording and monitoring children's DMDs.Conclusion In such developing countries as Iran, standard information recording and management is not properly done due to a large amount of information and the lack of comprehensive information registry systems. The findings of this study can help to design and establish information registry systems in the field of children's DMDs. Based on the findings of this research, it is recommended that future research be done to explore infrastructures necessary for providing a suitable platform to design and implement information registry systems in the field of children's DMDs.
Keywords: registry system; children's DMDs; data element